Upaya Peningkatan Kelola Keuangan di Kantin Dinas Pertanian Kabupaten Langkat - Nurhayati; Arisman; Frans Mikael Sinaga; Ronald Belferik; Tuti Andriani; Irfan Nainggolan; Suhendra Simangunsong (Cattleya Darmaya Fortuna, 2025)
The canteen is one of the key facilities that supports the activities of employees as well as visitors in government institutions. However, a frequent issue encountered is financial management, which is still recorded manually in notebooks and not properly documented. This community service program was conducted at the Canteen of the Department of Agriculture, Langkat Regency, with the aim of providing guidance in manual financial recording, cash flow management, and monthly financial reporting. The methods applied in this program included observation, socialization, training, and evaluation. The results indicated an improvement in the manager’s ability to prepare daily and monthly financial reports, understand income and expenditure flows, and implement a recording system using Microsoft Excel. Through this program, it is expected that the canteen managers will be able to maintain transparency and accountability, thereby ensuring the sustainability of the canteen’s operations effectively.